An introduction to the Greek New Testament: produced at Tyndale House, Cambridge - Jongkind, Dirk (Crossway, 2019)
"This guide will help starting readers make the most of the Greek New Testament Produced at Tyndale House, Cambridge. It provides a gentle introduction to its various features and to the theory and practice that informed the scholarly work behind the text. It also addresses issues such as textual variants, textual criticism, and the transmission and preservation of Scripture"--